2020
DOI: 10.15835/nbha48111784
|View full text |Cite
|
Sign up to set email alerts
|

Leaves anatomical and physiological adaptations of Vinca major ‘Variegata’ and Hedera helix L. to specific roof garden conditions

Abstract: Urban agglomerations create extreme microclimates for plants, in which growth, development and survival means adaptation. Plantations expansions beyond the typical gardens to buildings, walls or other build structures were realized in many cities with a rigorous selection of plant species. Although the number of woody species well adapted to the urban environmental conditions is quite large, few species manage to grow and develop on the roofs. Two species - Vinca major ‘Variegata’ and Hedera helix, regularly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The Vinca leaves contain different numbers of columnar palisade cells. It was confirmed that sunlight-grown plants have more columnar palisade cells than those of shade-grown plants [ 29 , 34 , 35 ]. Similar to our results where the indoor plants had a less differentiated palisade tissue than the outdoor plants, other studies showed that the palisade tissue cells in V. major var.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Vinca leaves contain different numbers of columnar palisade cells. It was confirmed that sunlight-grown plants have more columnar palisade cells than those of shade-grown plants [ 29 , 34 , 35 ]. Similar to our results where the indoor plants had a less differentiated palisade tissue than the outdoor plants, other studies showed that the palisade tissue cells in V. major var.…”
Section: Discussionmentioning
confidence: 99%
“…There are quantitative and qualitative differences regarding the chemical composition of Vinca extracts, and previous studies showed that the morphological and anatomical traits of the leaves (shape and surface, cuticle, stomata, trichome, epidermis, etc.) are responsible for the chemical composition variability in the extracts [ 33 , 34 , 35 , 36 ]. These morphological and anatomical aspects of the Vinca leaf had been investigated in this study as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations